The Effect Of Gingivitis In Elderly Patients Compared With Young Patients And Impact Of Factors In Different Age Groups - Hussein, Hajir Hassan; Alawadi, Anfal Ihsan Jasim; Kzar, Hatem Kareem (Medical Science Journal for Advance Research, 2024)
Background: Gingivitis/periodontitis is one of the widespread chronic diseases affecting the supporting structures of teeth, specifically the part of the gum that surrounds the base of the teeth. Method: The present study was involved 294 patients who were coming to Specialized Dental Center, (206) (68.8%) patients were coming for extraction of teeth while (94) (31.4%) were approached for filling teeth in specialist dentist. The data of the current research was collected from the patients who visited the Specialized Dental Center in the city of Al-Diwaniyah during the period from 1st Sept. to 31th Oct.-2021. Results: The results of current investigation were included 294 patients, 206 (68.6%) patients were visited dental clinic for teeth extraction whereas, only 94 (31.4%) coming for filling teeth. As well as the percentage of gingivitis in dental patients which involved (106) (51%) suffering g from high level in gingivitis while (100) (48%) patients do not suffer from gum inflammation. Or over , there are multiple factors responsible for gingivitis such as smoking that was regarded as high rate about (41%) while only (24%) have a chronic disease and finally about (35%) patients have gingivitis because avoided brush teeth that mean bad oral hygiene, the male group reported (71) (67%) patients which significantly more than female group that reported lower percentage about ( 35) (33%) patient suffering from gingivitis .finally, one of the most important results were Age groups of gingivitis patients were illustrated that the first age group (11-25 years ) showed 16%, and the second age group (21-30) represented high percent about 51% which considered of the most important results which unexpected, and the third group (31- 40) presents 26%. in contrast to above this fourth group provides low level only 7%, this results one of the different results in multi-label pervious researches. Conclusion: The results of this investigation show that the most interesting finding was concluded that the young patients the most infected with gingivitis compared with elderly patients, this is an important issue for future research. These results were important to understanding what’s the immunological different in young compared with aged group that lead increase level of infection by gingivitis.